Field guide to the commercial marine and brackish-water resources of the northern coast of South America - Cervigon, F. ...[et al] (FAO RomeIT, 1993)
Provides a qualified, illustrated inventory of species of current or potential interest to fisheries occuring in the area; the essential technical information required for correct field identification of families and species of interest to fisheries; and basic information on distribution, habits and fisheries for each family and species.